The Loose Interpretation of Dominus Litis Principle in Marriage Dispensation for Underage Marriage in Banten - Ishom, Muhammad (Universitas Islam Negeri Jakarta, 2023)
The judges of Religious Courts play a crucial role in reducing underage marriages. The judges can consider marriage dispensation by emphasizing the principle of dominus litis, which can be understood as a case controller. Since the Religious Courts in Banten have granted considerable dispensation appeals, the early-age marriages have increased significantly. This research examines the implementation of the dominus litis principle and the difficulties in establishing the grounds for urgent marriage dispensation. The data were collected via observations and interviews with the judges, former judges, lawyers, and societies. This research employs the juridical-empirical research technique, examining several facts and data generated by the public. The study reveals that to approve marriage dispensation, the judges of ReligiousCourts merely focus on the legal truth from the applicants’ statements, the underage marriage candidates, witnesses from applicants’ immediate families, and document evidence presented with the application. Judges rarely summon additional witnesses from specialists and professionals focusing on the children’s issues, which might strengthen formal legal evidence. The court granted the request to safeguard the children from immoral behavior, contradicting the common public ethics and morals and ignoring a significant principle of dominus litis. Abstrak: Hakim Pengadilan Agama memiliki peran penting untuk menekan kasus perkawinan dini. Hakim dapat mempertimbangkan dispensasi nikah dengan menekankan prinsip dominus litis, yaitu hakim sebagai pengendali perkara. Sejak permohonan dispensasi banyak dikabulkan oleh pengadilan agama di Banten, perkawinan dini di Banten mengalami peningkatan secara signifikan. Studi ini menganalisis penerapan